Peran Gaya Kepemimpinan terhadap Motivasi dan Kinerja Karyawan di PT. Infineon Technologies Batam - Yulinda Tarigan; Mangaraja Sahat Parulian Pandiangan (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
The purpose of this research is to examiine the effect of leadership style on employee motivation and performance at PT. Infineon Technologies Batam. The variables of this research are work motivation (X1) and employee performance (X2). The research approach uses quantitative and uses classical assumption test, multiple linear regression, T test and F test. The population and research sample are 88 respondents. Data collection for this study used a questionnaire consisting of 11 items/indicator statements. The results with a significance level of 0.05 indicate that leadership style has a positive and significant effect on employee work motivation where Tcount 8,770 > Ttable 1,98827 and leadership style does not have a positive and significant effect on employee performance where Tcount 0.426 < Ttable 1.98827. In addition, leadership style has a positive and significant influence on motivation and performance simultaneously. Therefore, after the conclusion of this study, the suggestion from the researcher is to increase the salary/wages to employees or to get an increase in the form of allowances or bonuses for the amount of overtime and increase the number of employees in doing the parts that do require more attention.